Communication Strategies: The Fuel for Quality Coach-Athlete Relationships and Athlete Satisfaction - Davis, Louise; Jowett, Sophia; Tafvelin, Susanne (Frontiers in Psychology, 2019)
The present two-study paper examined the role of communication strategies that athletes use to develop their coach-athlete relationship. Study 1 examined the mediating role of motivation, support and conflict management strategies between the quality of the coach-athlete relationship and athletes’ perceptions of sport satisfaction. Study 2 examined the longitudinal and mediational associations of communication strategies and relationship quality across two time points, over a six-week period. Within both studies, data were collected through multi section questionnaires assessing the studies’ variables. For study 1, structural equation modelling highlighted significant indirect effects for motivation and support strategies between the quality of the coach-athlete relationship and athletes’ experiences of sport satisfaction. For study 2, significant indirect effects were found for the athletes’ perceptions of the quality of the coach-athlete relationship at time 2 between athletes’ use of communication strategies at time point 1 and time point 2. Together these findings provide support for the practical utility of communications strategies in enhancing the quality of the coach-athlete relationship and athlete’s experiences of sport satisfaction. In addition, the findings provide evidence to highlight the potential cyclical relationship between communication and relationship quality across time.